Réponses

Meilleure réponse !
2014-03-25T00:44:33+01:00
Bonsoir,

f(x) ≤ 6
-3x(x + 4) ≤ 6
-3x² - 12x ≤ 6
-3x² - 12x - 6 ≤ 0
3x² + 12x + 6 ≥ 0
x² + 4x + 2 ≥ 0
x² + 4x + 4 - 4 + 2 ≥ 0
(x² + 4x + 4) - 4 + 2 ≥ 0
(x + 2)² - 2 ≥ 0
(x + 2)² - (√2)² ≥ 0
(x + 2 + √2)(x + 2 - √2) ≥ 0

Racines : x + 2 + √2 = 0 ==> x = -2 - √2
               x + 2 - √2 = 0  ==> x = -2 + √2

\begin{array}{|c|ccccccc|}x&-\infty&&-2-\sqrt{2}&&-2+\sqrt{2}&&+\infty \\ x+2+\sqrt{2}&&-&0&+&+&+&\\ x+2-\sqrt{2}&&-&-&-&0&+&\\ Produit&&+&0&-&0&+&\\ \end{array}\\\\\\S=]-\infty;-2-\sqrt{2}]\ \cup\ [-2+\sqrt{2};+\infty[
Voilà, j'ai effacé le début :)
Merci beaucoup !
La seule erreur est que -3x(x+4) = -3(x)2 + 12x
Non Hiphigenie a raison car on multiplie -3x par 4 ce qui donne -12x
Hé oui,! -3x(x+4) = -3x² - 12x. :)